Quality Changes in Pearl Millet Based Pasta during Storage in Flexible Packaging - Jalgaonkar, Kirti; Jha, S. K.; Nain, Lata; Iquebal, Mir Asif (Journal of Agricultural Engineering, 2018)
Pearl millet based pasta was evaluated for quality changes during 6-month storage in bi-axially oriented polypropylene (BOPP) packaging material of 100 μm thickness and water vapour transmission rate of 7.71 g,m-2.day-1 at ambient condition (32.95 ± 8.75 °C (max), 17.6 ± 12.1 °C (min) and 79 ± 19 % RH). The quality parameters of pasta were determined at intervals of 1 month. Moisture content (MC) of pasta varied from 8.87 % to 11.90 %, water activity 0.51 to 0.66, free fatty acids (FFA) 0.48 % to 0.82 %, peroxide value (PV) 2.10 to 5.79 meq.kg-1 of oil, fat acidity 20.54 mg.100 g-1 to 37.77 mg.100 g-1. Cooking loss (6.22 % to 7.66 %) and variation in textural properties such as hardness (10.75-11.68 N), cohesiveness (0.60-0.64), springiness (1.17-1.26 mm), gumminess (6.01-6.45 N), chewiness (6.15-6.45 N.mm) of pasta were found to be non-significant during storage period. Moisture content, water activity, FFA, PV, fat acidity were found to be positively related to storage period. Microbial counts (total plate count, yeast, mould, E. Coli, Salmonella, Shigella) were not detected during the entire storage period. With overall acceptability value of 7.67 out of 9, the sensory evaluation revealed very good acceptability of the product even after 6 months of storage. Thus, the overall quality, safety, and acceptability of the product remained acceptable throughout the 6-month storage period.